SEIPS 3.0: Human-centered design of the patient journey for patient safety. (April 2020) - Carayon, Pascale; Wooldridge, Abigail; Hoonakker, Peter; Hundt, Ann Schoofs; Kelly, Michelle M.
Abstract: The Systems Engineering Initiative for Patient Safety (SEIPS) and SEIPS 2.0 models provide a framework for integrating Human Factors and Ergonomics (HFE) in health care quality and patient safety improvement. As care becomes increasingly distributed over space and time, the "process" component of the SEIPS model needs to evolve and represent this additional complexity. In this paper, we review different ways that the process component of the SEIPS models have been described and applied. We then propose the SEIPS 3.0 model, which expands the process component, using the concept of the patient journey to describe the spatio-temporal distribution of patients' interactions with multiple care settings over time. This new SEIPS 3.0 sociotechnical systems approach to the patient journey and patient safety poses several conceptual and methodological challenges to HFE researchers and professionals, including the need to consider multiple perspectives, issues with genuine participation, and HFE work at the boundaries. Highlights: The patient journey represents patient interactions with multiple health care contexts distributed over space and time. The patient journey is composed of multiple local work systems embedded in interconnected care settings. Improving safety in the patient journey poses challenges for HFE, e.g. genuine participation of multiple stakeholders.